Seismic, Field, and Remote Sensing Analysis of the 13 February 2024 Çöpler Gold Mine Landslide, Erzincan, Türkiye - Pınar Büyükakpınar; Angela Cristina Carrillo-Ponce; Muhammad Badar Munir; Ezgi Karasözen; Hakan Tanyas; Deniz Ertuncay; Athul Palliath; Tolga Gorum (The Seismic Record)
A massive landslide (1–1.2 Mm3) struck the Çöpler Gold Mine in Erzincan, Türkiye, on 13 February 2024 (∼11:30:10 UTC), and killed nine buried miners under a heap leach pad. The landslide was recorded at seismic stations up to 400 km away, with two distinct pulses 48 s apart. These pulses were analyzed using a single-force model with Bayesian bootstrap-based probabilistic inversion, providing insight into the complex forces driving the landslide. This landslide consisted of two mass movements: (F1) westward detachment on a steep slope and (F2) north-northeast movement on a gentler slope, with significant impacts consistent with field observations and optical imagery. Interferometric Synthetic Aperture Radar detected continuous slow deformation over four years at mean rates of up to 60 mm/yr. The cyanide leach pond exhibits critical 85 mm/yr deformation with the risk of environmental contamination because it contains poisonous waste and is located close to the Euphrates River. This study stresses that seismological monitoring and infrastructure resilience are crucial factors in active mining areas.